Sustainable Improvement of Expansive Clays Using Xanthan Gum as a Biopolymer - Joga, Jayaprakash Reddy; Varaprasad, B.J.S. (Civil Engineering Journal, 2019)
In this study, Biopolymers are used as an attempt to create sustainable environment by eliminating the negative environmental impacts of using traditional admixtures in soil stabilization. Xanthan Gum is used as a biopolymer to treat expansive soil. A series of tests like, Standard Proctor Test, Unconfined Compressive Strength (UCS), One-Dimensional Consolidation and Standard Direct Shear tests were conducted on virgin soil and biopolymer (0, 0.5, 1, 1.5, 2, 2.5%) treated soils. The results revels that by addition of biopolymer content Maximum Dry Density (MDD) of soil decreases and Optimum Water Content (OMC) increases. The UCS value is increased by 4 times for the addition of 1% xanthan gum to soil for 28 day curing period. Compressibility of soil is deceased by 65% for 28day curing period. Shear parameters of treated soil shows improvement with addition of xanthan gum content. For further examination, SEM analyses were conducted on the tested samples and revealed that the soil fabric had white lumps and pores in the soil structure were filled with cementitious gel. Moreover, the resistance towards shear and compressibility of treated samples increased with curing times. Therefore, use of Xanthan Gum for soil stabilization is a solution for eco-friendly soil stabilizing material.